2022
DOI: 10.1186/s40249-022-00988-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of human social contact and mask wearing in high-risk groups in China

Abstract: Background The pandemic of coronavirus disease 2019 (COVID-19) has changed human behavior in areas such as contact patterns and mask-wearing frequency. Exploring human–human contact patterns and mask-wearing habits in high-risk groups is an essential step in fully understanding the transmission of respiratory infection-based diseases. This study had aims to quantify local human–human (H–H) contacts in high-risk groups in representative provinces of China and to explore the occupation-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…This hypothesis suggests that people adhere less to close people, consistent with Strickland et al (2022). Also, our results were consistent with Al Naam et al (2021) about lower mask-wearing in social gatherings (likely indoor context), and Zheng et al (2022) about more risky behavior was more likely to occur at home or among family members (likely indoor context). The contexts we selected for this study were not specific enough to determine stimulus control topographies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This hypothesis suggests that people adhere less to close people, consistent with Strickland et al (2022). Also, our results were consistent with Al Naam et al (2021) about lower mask-wearing in social gatherings (likely indoor context), and Zheng et al (2022) about more risky behavior was more likely to occur at home or among family members (likely indoor context). The contexts we selected for this study were not specific enough to determine stimulus control topographies.…”
Section: Discussionsupporting
confidence: 91%
“…Adherence to protective behaviors was sensitive to social contexts and situations (English & Li, 2021;Zheng et al, 2022). In some situations, people adhered more than in others.…”
Section: Protective Behaviors Against Covid-19mentioning
confidence: 99%
“…As airborne diseases continue to emerge, mask use is still suggested in public and work spaces as a precautionary measure. In China, mask use remains a highly adopted practice in everyday life . However, studies on the adverse effects of wearing masks yielded inconsistent conclusions due to short duration of intervention .…”
Section: Introductionmentioning
confidence: 99%
“…The control measures for the COVID-19 outbreak were based on the biological characteristics of SARS-CoV-2 and intended for long-term application [2,14]. Previous expertise promoted the idea that herd immunity could be achieved as long as the vaccine coverage rate reached a critical value of over 80% [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of new mutant variants, the imbalance of global vaccine distribution, and breakthrough infections in vaccinated populations have brought continuous challenges to the effectiveness of vaccinations, resulting in the inability to form a population-wide persistent immune barrier in the shortterm [19,20]. Non-drug interventions such as social distancing, mask-wearing, cleaning hands, and avoiding crowds remain the main prevention and control measures [14,21]. Studies found that social distancing, including the cancellation of small gatherings and the closure of educational institutions, as well as travel and border restrictions, had the greatest impact on preventing and controlling COVID-19 outbreaks of all existing non-drug interventions [2,18,22].…”
Section: Introductionmentioning
confidence: 99%